ZAKAT PRODUKTIF SEBAGAI ALTERNATIF KREDIT MIKRO DALAM PENGEMBANGAN USAHA MUSTAHIK (STUDI KASUS UPZ UNIB) - Reno Adi Saputra; Ratu Eva Febriani (Convergence: The Journal of Economic Development, 2019)
This research aims to know the impact of zakat funds allocation to the business economy of the recipent (Mustahik) given by UPZ Unib, the progress of capital,  the progress t of omset and the progess of advantages. The data used are primary data. The method  analysis used in this research is descriptive analysis quantitative. The results of this research show that the allocation of produvtive zakat funds have impact on business omset with an average progress capital of 43.53%, the progress of business omset with an average of 41.71%, and the progress of average business profits 37.75% Keywords : Capital, Mustahik Business, Omset, Professional zakat, Profit, UPZ Unib